Public health and clinical implications of Dobbs v. Jackson for patients and healthcare providers: A scoping review. - David T Zhu; Lucy Zhao; Tala Alzoubi; Novera Shenin; Teerkasha Baskaran; Julia Tikhonov; Catherine Wang (PLoS ONE)
Introduction On June 24, 2022, the U.S. Supreme Court's decision in Dobbs v. Jackson reversed the precedent set forth by Roe v. Wade, empowering individual states to regulate abortion care. This aftermath of this ruling has given rise to widespread bans, limiting the accessibility of abortion services for patients and impeding providers' ability to deliver a comprehensive spectrum of reproductive health services. Of particular concern is the disproportionate impact on medically underserved groups, further heightening existing social and structural disparities in reproductive health. Methods We conducted a scoping review to broadly evaluate the clinical and public health impact of Dobbs on patients' access to abortion care and related reproductive health services, in addition to the training and clinical practice of healthcare providers. We searched eight bibliographic databases (PubMed, Scopus, Embase, PsycINFO, Google Scholar, Science Direct, JSTOR, and Web of Science) and three preprint servers (medRxiv, bioRxiv, and Europe PMC) using various combinations of keywords related to 'abortion', 'Dobbs', and 'Roe' on March 22, 2023. Four reviewers independently screened the studies based on pre-specified eligibility criteria and one reviewer performed data extraction for pre-identified themes. The search was conducted based on PRISMA Extension for Scoping Reviews (PRSIMA-ScR) guidelines. Results Eighteen studies, comprising 12 peer-reviewed articles and 6 study abstracts, met the inclusion criteria. The studies demonstrated that Dobbs increased demand for contraception, magnified existing travel- and cost-related barriers to access, further polarized views on abortion and complex family planning on social media (e.g., Twitter), and evoked substantial concerns among medical trainees regarding their scope of practice and potential legal repercussions for providing abortion care. Conclusion In the wake of Dobbs v. Jackson, further public health and clinical interventions are urgently needed to bridge disparities in abortion care and reproductive health, mitigating the deleterious consequences of this emerging public health crisis.